2021
DOI: 10.1371/journal.pone.0246636
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular flow alterations in critically ill COVID-19 patients: A prospective study

Abstract: Background Data on microcirculatory pattern of COVID-19 critically ill patients are scarce. The objective was to compare sublingual microcirculation parameters of critically ill patients according to the severity of the disease. Methods The study is a single-center prospective study with critically ill COVID-19 patients admitted in ICU. Sublingual microcirculation was assessed by IDF microscopy within 48 hours of ICU admission. Microcirculatory flow index (MFI), proportion of perfused vessel (PPV), total ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The function of the sublingual microcirculation, on the other hand, directly reflects the oxygen delivery capacity to the tissue, and has previously been shown to tightly correlate with the outcome in critically ill patients [ 30 , 31 ]. The increased microcirculatory functional capacity found in the present study is consistent with previous findings [ 2 , 32 , 33 ] and has been shown to persist until the occurrence multi-organ failure [ 2 , 32 ] or severe endothelial dysfunction [ 34 , 35 ]. However, in contrast to previous measurement methods of microcirculatory function such as subjective classification of image sequences and assignment of mean flow index (MFI) categories, the quantitative, fully automated, algorithm-based image sequence analysis enabled by MicroTools and used in the present study, allowed for accurate quantification of the functional microcirculatory hemodynamic variables, as well as the elimination of inter-observer bias introduced by subjective grading [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
“…The function of the sublingual microcirculation, on the other hand, directly reflects the oxygen delivery capacity to the tissue, and has previously been shown to tightly correlate with the outcome in critically ill patients [ 30 , 31 ]. The increased microcirculatory functional capacity found in the present study is consistent with previous findings [ 2 , 32 , 33 ] and has been shown to persist until the occurrence multi-organ failure [ 2 , 32 ] or severe endothelial dysfunction [ 34 , 35 ]. However, in contrast to previous measurement methods of microcirculatory function such as subjective classification of image sequences and assignment of mean flow index (MFI) categories, the quantitative, fully automated, algorithm-based image sequence analysis enabled by MicroTools and used in the present study, allowed for accurate quantification of the functional microcirculatory hemodynamic variables, as well as the elimination of inter-observer bias introduced by subjective grading [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
“…To date, a number of studies have investigated the sublingual microcirculation in COVID-19 patients [17][18][19][20][21][22][23] A first evaluation conducted by Damiani et al [17] in 12 patients with COVID-19 pneumonia showed that sublingual microvascular capillary densities were inversely correlated with D-dimer levels, suggesting the impact of microthrombosis on the microcirculatory function. In a prospective observational study [20], Kanoore Edul et al demonstrated that sublingual microcirculation in severe COVID-19-ARDS patients was characterized by decreases in PPV (0.96 ± 0.03) and flow quality (MFI: 2.79 ± 0.10 and red blood cell velocity: 1124 ± 161 µm/s) along with high vascular densities (TVD: 21.9 ± 3.9 and PVD: 21.0 ± 3.5 mm/mm 2 ), compared to normal values.…”
Section: Introductionmentioning
confidence: 99%
“…Present observations are in line with the available evidence showing an abnormal capillary density and/or function in COVID-19 patients. Previous studies have suggested that COVID-19 patients have reduced flow reserve in the forearm skin, as well as reduced microcirculatory flow index and perfused vessel density in the sublingual circulation (29)(30)(31). Interestingly, in one of these observations Sabioni et al have observed that peak hyperemic flow was impaired in either moderate or severe COVID-19 patients, but basal flow velocity was only affected in patients with severe COVID-19 (31).…”
Section: Discussionmentioning
confidence: 98%